2020
DOI: 10.1080/12298093.2020.1765719
|View full text |Cite
|
Sign up to set email alerts
|

Seventeen Unrecorded Species from Gayasan National Park in Korea

Abstract: Macrofungi play important roles in forest ecology as wood decayers, symbionts, and pathogens of living trees. For the effective forest management, it is imperative to have a comprehensive overview of macrofungi diversity in specific areas. As a part of the National Institute of Biological Resources projects for discovering indigenous fungi in Korea, we collected macrofungi in Gayasan National Park from 2017 to 2018. These specimens were identified based on morphological characteristics and sequence analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
3
0
1
Order By: Relevance
“…To date, seven species in section Sclerotiora have been reported in Korea: P. adametzioides, P. cainii , P. daejeonium , P. herquei , and P. sclerotiorum from terrestrial environments [17,18,25,26] and P. bilaiae and P. viticola from marine environments [12,13]. Through this study, we found eight species from marine environments.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…To date, seven species in section Sclerotiora have been reported in Korea: P. adametzioides, P. cainii , P. daejeonium , P. herquei , and P. sclerotiorum from terrestrial environments [17,18,25,26] and P. bilaiae and P. viticola from marine environments [12,13]. Through this study, we found eight species from marine environments.…”
Section: Resultsmentioning
confidence: 72%
“…Currently, 30 species have been described in this section [21–24]. In Korea, seven species have been reported: five species from terrestrial environments [17,18,25,26] and two from marine environments [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…To date, 66 milkcap species have been reported in South Korea [ 42 ]. These specimens were identified based solely on morphology and many European and North American names were used [ 23 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…주로 정원에 식재되거나 습지 에 분포하는 대표적인 수생식물로서 [9] 잎은 마주나며 물위에 뜨고, 꽃은 6-9월에 황색으로 잎겨드랑이(葉緣)에서 하나씩 핀 다. 예로부터 민간요법으로 뱀독, 해열, 항경련 등의 치료에 사 용되었고 우리나라에는 어리연꽃, 노랑어리연꽃, 좀어리연꽃 3 종이 자생한다 [10]. 기존에 보고된 연구로는 '노랑어리연꽃 잎 에서 분리된 성분의 약리학적 효과 [11]…”
Section: 서 론unclassified